ANALISIS PERBEDAAN KINERJA BANK PEMERINTAH DAN BANK UMUM SWASTA (Students' Journal of Accounting and Banking, 2012)
The calculation of the ratio is very important for outsiders who want to assess a company's financial statements. Therefore conducted a study to measure the performance of banks through liquidity ratio approach, solvency, and profitability of the Government and the Bank Private Bank.The study was conducted with a view to determining whether or not differences in financial performance, including Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Return On Assets (ROA), Return On Equity (ROE), Non PerformingLoan (NPL), Operating Costs (BOPO) on the Government and the Bank's Private Bank.The population in this study were government banks andprivate banks listed in the report of BEI tahun 2003-2010.Sample selection method used is purposive sampling technique. Data analysis technique used is the analysis of different testMann-Whitney test.The results of this study can be concluded that: (1) No difference between the CAR, NIM and NPL Government and Bank Private Bank. (2) There is a difference between the ROA, ROE, BOPO Bank Government and Private Banks.Keywords: Capital Adequacy Ratio, Net Interest Margin, Return On Assets (ROA), Return On Equity, Non PerformingLoan (NPL), Biaya Operasional (BOPO)